Bone marrow morphological examination an analysis of 500 cases (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Examination of peripheral blood film (PBF) and biopsy of the bone marrow are an indispensible adjunct to the study of diseases of the blood and may be the only way in which a correct diagnosis can be made. Marrow can be obtained by needle aspiration, percutaneous trephine biopsy or surgical biopsy. Morphological examination of the bone marrow by an experienced haematologist can provide very useful information important for many haematological and non-haematological disorders. Objective: The aim of the study was to diagnose both haematological and non-haematological disorders by only morphological bone marrow examination in a district town distant from the capital city where sophisticated diagnostic facilities are not available. Methods: This cross sectional type of descriptive study was carried out in Combined Military Hospital (CMH), Jessore and different private and public hospitals. Five hundred cases taken as a non-probability purposive sampling method were included in this study irrespective of age and sex from January 2009 to June 2011. Bone marrow was aspirated from posterior superior iliac spine and first piece of the body of the sternum taking aseptic precautions and after infiltrating local anaesthesia. Only two cases required percutaneous trephine biopsy. After aspiration bone marrow smears were stained and examined under microscope. 59 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Results: There were 294 (58.8%) male and 206 (41.2 %) female out of 500 cases. The age of the patients ranged from one year to 82 years. Haematological malignancy were 321 cases (64.2%), non-malignant haematological and non-haematological diseases were 112 (22.4%) and 56 (11.2%) cases respectively and normal active marrow were from 11 (2.2%) cases. Among 321 haematological malignancies, Acute Lymphoblastic Leukaemia (ALL) and Acute Myeloblastic Leukaemia (AML) were 126 (39.3%) and 99 (30.8%) respectively and Chronic Myeloid Leukaemia (CML) were 37 (11.5%). Out of 112 non-malignant haematological cases, erythroid hyperplasia was found in 42 (37.5%) cases in which micronormoblastic erythroid hyperplasia was 33 (29.5%) and megaloblastic erythroid hyperplasia was 9 (8.0%) cases. Aplastic anaemia/progressive marrow failure was diagnosed in 40 (35.7%) cases. Two (1.8%) cases were diagnosed as myelofibrosis. Non-haematological diseases were 56 of which 49 (87.5%) cases were secondary reactive marrow & only seven (12.5%) cases were secondary metastatic deposits in the bone marrow. Conclusion: Morphological examination of bone marrow aspirate is a key to the diagnosis of many diseases especially the haematological disorders. Microscopic examination of bone marrow aspirate by an experienced haematologist may solve many diagnostic difficulties faced in day to day clinical practice. Therefore, for the betterment of both patients and physicians more emphasis should be given to become well conversant in reporting a bone marrow aspirate by the haematologists. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21828 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013